Interpretations of the Name Israel in Ancient Judaism and Some Early Christian Writings : From Victorious Athlete to Heavenly Champion. - Hayward, C. T. R. (Oxford University Press, UK, 2005)
Ancient peoples regarded names as indicative of character and destiny. The Jews were no exception. All Jews descended from Jacob, who was given the name Israel. The Bible seemed to explain this name as having to do with struggle. But generations following the Bible found in Israel references to seeing God, singing, ruling, being upright, angelic qualities, and much more besides. This book examines those explanations, and attempts to show how they came to be adopted and. why. - ;Ancient peoples regarded names as indicative of character and destiny. The Jews were no exception. This is a critical.